감염성 척추염과 감별질환의 병태생리와 MRI 소견 - 유선진; 김여주; 이승훈; 류정아; 박성훈; 홍정의; Sunjin Ryu; Yeo Ju Kim; Seunghun Lee; Jeongah Ryu; Sunghoon Park; Jung Ui Hong (Taehan Yŏngsang Ŭihakhoe chi, 2021)
On MRI, abnormal signals of the intervertebral disc, destruction of the upper and lower vertebral body endplate around the disc, and bone marrow edema around the endplate are considered typical findings of infectious spondylitis. These findings can also appear in various non-infectious spinal diseases, such as degenerative changes, acute Schmorl's node, spondyloarthropathy, synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO), chronic recurrent multifocal osteomyelitis, and calcium pyrophosphate dihydrate crystal deposition disease. The imaging findings of infectious spondylitis that can be differentiated from these non-infectious spinal diseases on MRI are high signal intensity and abscess of the disc space, an abscess in the paraspinal soft tissue, and the loss of the linear low signal intensity on T1-weighted images of the bony endplate. However, these differentiation points do not always apply since there are many similarities in the imaging findings of infectious and non-infectious diseases. Therefore, for an accurate diagnosis, it is important to know the imaging characteristics related to the pathophysiology of not only infectious spondylitis but also non-infectious spinal diseases, which requires differentiation from infection. MRI에서 추간판의 이상 신호와 위, 아래 척추체 종판의 파괴, 종판 주변의 골수부종 등은 감염성 척추염의 전형적인 소견으로 여겨지나 퇴행성 척추질환, acute Schmorl's node, 척추관절병증, synovitis, acne, pustulosis, hyperostosis, and osteitis (SAPHO)/chronic recurrent multifocal osteomyelitis, 척추신경관절병증, calcium pyrophosphate dehydrate 결절침착질환 등 다양한 비감염성 척추질환에서도 나타날 수 있다. MRI에서 이러한 비감염성 척추질환과 감별되는 감염성 척추염의 영상 소견은 추간판의 고신호와 농양, 척추 연부조직의의 농양, 그리고 T1 강조영상에서 저신호로 보이는 종판의 경계가 불명확해지는 점 등이다. 그러나 이러한 감별점이 항상 적용되는 것은 아니며 감염성, 비감염성 질환의 영상 소견에 유사점이 많기 때문에 정확한 진단을 위해서는 감염성 척추염뿐만 아니라 감염과 감별해야 하는 다양한 질환의 병태생리와 연관된 영상학적 특징을 아는 것이 중요하다.